Does Catchment Nestedness Enhance Hydrological Similarity?. Issue 13 (8th July 2021) - Betterle, A.; Botter, G.
Abstract: The topology of river networks defines the hierarchical organization of the landscape and controls the drainage pathways triggered by precipitation. This study investigates how the structure of channel networks influences spatial patterns of flow regimes by focusing on the hydrograph observed at the outlet of nested and non‐nested basins. An extensive data set spanning diverse geomorphoclimatic conditions is used to show that – when inter‐catchment distance increases – nested catchments exhibit a more pronounced decrease of streamflow correlation as compared to non‐nested sites. Thus, non‐nested basins have more correlated hydrologic responses at large distances. This unexpected behavior is explained by a geometrical model, which reveals that inter‐catchment differences in size and elevation are larger in nested sites, thereby increasing the spatial heterogeneity of key hydrological processes that shape the hydrograph. This study provides clues to critically reinterpret the hydrological response on nested versus non‐nested catchments, with relevant implications for hydrology and ecology. Plain Language Summary: Streams and rivers originate when the landscape drains after precipitation events. Differences in streamflow magnitudes result from the spatial variability of precipitation, soil and vegetation properties, and from the geometry of drainage networks. From a geometrical perspective, two catchments can be either nested (if the smaller is embedded into the larger one) or non‐nested (if the corresponding contributing areas are non‐overlapping). Nested catchments are commonly assumed to be hydrologically more similar just because they are hydraulically connected. However, we show that this is not true in general. In fact – as the distance between two catchments increases – streamflow regimes in nested catchments lose similarity faster as compared to non‐nested sites. This unexpected behavior is here explained through a geometrical model, which reveals how couples of nested catchments are systematically more different in terms of contributing area, elevation, and slope. Recognizing the enhanced diversity of nested catchments can help to better predict and interpret spatial patterns of water resources along river systems, with relevant implications for water management and ecosystem services. Key Points: Nested catchments are less hydrologically similar than non‐nested catchments if inter‐catchment distance is explicitly considered Nested catchments are more heterogeneous in terms of size, slope, and elevation as compared to non‐nested catchments Challenging the widespread idea that nested catchments are hydrologically similar is relevant for ecology and water resources monitoring